Perspective on salutogenic approaches to persistent pain with a focus on mindfulness interventions - Paley, Carole A.; Johnson, Mark I. (Frontiers in Pain Research, 2023)
In this perspectives article, we provide a unique perspective on the use of mindfulness interventions in a whole health framework embedded within the theory of salutogenesis and the concept of painogenic environments. We argue that mindfulness is a valuable tool to bridge exploration of inner experiences of bodily pain with socio-ecological influences on thoughts and emotions. We outline research from neuroimaging studies that mindfulness techniques mediate neural processing and neuroplastic changes that alleviate pain and related symptoms. We also reviewed evidence examining behavioural changes associated with mindfulness meditation providing evidence that it promotes self-regulatory activity, including the regulation and control of emotion and catalysation of health behaviour changes; both of which are important in chronic illness. Our viewpoint is that mindfulness could be a core element of salutogenic approaches to promote health and well-being for people living with pain because it rebuilds a fractured sense of cohesion and underpins an ‘ecology of wholeness’ which could mitigate the detrimental consequences of painogenicity. Mindfulness empowers people in pain to embrace their existence; shifting the focus away from pain and giving their lives meaning. We propose that integrating mindfulness into activities of daily living and individual or community-based activities will promote living well in the modern world, with or without pain; thus, promoting individual potential for fulfilment. Future research should consider the effects of mindfulness on people with pain in real-life settings, considering social, environmental, and economic factors using a broader set of outcomes, including self-efficacy, sense of coherence and quality of life.